“Russian Grain” and the Agrarian Oganizations in the Early ХХ Century. - Лисенко, Майя (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The purpose of the article is to study the activities of the “Russian Grain” society on the development of agriculture in the Russian Empire. The author analyzed that it was founded to support the agrarian reform of P. A. Stolypin. “Russian Grain” had a more practical focus than other agricultural societies. It was provided with all possible assistance from the government and the heads of the agricultural department. The researcher draws attention to the fact that the main direction of work included training of peasants abroad in model farms. Landowners had an opportunity to improve their knowledge and practice. The company cooperated with other agrarian organizations. The author made a comparative description of the activities of the association. “Russian Grain” with the Petersburg Assembly of Rural Owners and the Northern Agricultural Society. The article also explored the relationship with the public agrarian organizations of the Ukrainian provinces. The “Russian Grain” actively propagated the idea of ​​borrowing useful and necessary foreign experience. The society had far-reaching plans. However, the situation was complicated by the consequences of the events of 1905-1907, the instability of the economy. The “Russian Grain” ceased to exist with the collapse of the Russian Empire in 1917. The author made a conclusion about the effectiveness and prospects of the activity of this agrarian organization.